What we talk about when we talk about space: End user participation between processes of organizational and architectural design - Marianne Stang Våland (Copenhagen Business School (CBS), 2010)
In the thesis, I explore the construction of mutual links between two design processes that have traditionally been considered separated and sequentially organized: the organizational and the architectural design processes. The general background for the study is the increasing interest in space and architecture as a potential strategic vehicle that has established within contemporary management during recent years. Scholars within organization studies seem to share this interest. However, only few research contributions are based on empirical studies. My aspiration with the thesis is to contribute to fill this gap.
hdl:10398/8002
Keywords: 650